Innovative Leader Development Evaluation of the U.S. Army Asymmetric Warfare Adaptive Leader Program - Straus, Susan G. (RAND Corporation, 2014)
The U.S. Army's Asymmetric Warfare Adaptive Leader Program is designed to enhance adaptive performance in leaders and promote innovative solutions in training. This report describes results of a systematic evaluation of the program, offers recommendations for improvement, and provides recommendations for ongoing evaluation of this program and other courses or events that address adaptive performance and acquisition of other intangible skills.